Academic Online Platforms and the Hungarian “Netizen” Youth: Theoretical Framework and Empirical Research on General Usage Patterns - Márton Iványi (Youth, 2024)
In parallel with their counterparts in neighboring countries, specifically Slovakia, the Czech Republic, and Poland, Hungarian university students also exhibit a high level of involvement in internet activities, particularly within the realm of online social networking. Our quantitative data analysis, in line with our primary hypothesis, reveals a substantial proportion of university students displaying additional awareness also of academic online platforms (hereinafter: AOPs) specifically. These platforms, as per our typology, encompass the following categories: (1) academic online social networking sites; (2) databases lacking social features; and (3) author profiles linked to publishers. Notably, student awareness is most prominently affiliated with academic social networking sites offering comprehensive access to full-paper views. The data gathered in the framework of qualitative research was based on a contingent of 100 university respondents’ (mostly female residents of the capital Budapest) answers to seven demographic and thematic questions The corresponding findings further indicate that, with the exception of a notable segment actively engaging with these AOPs, the majority of students exhibit sporadic usage patterns concentrated during specific seasonal peaks. At the same time, author profiles linked to publishers currently remain beyond the immediate reach of the broader student population.